Transcriptomic and proteomic analyses of Weissella koreensis isolated from kimchi with different growth-limiting temperatures - Hye In Ko; So-Rim Kim; Moeun Lee; Chae-Rim Jeong; Nuri Na; Jong-Bang Eun; Tae-Woon Kim (Food Research International, 2026)

Reassembled yeast vacuoles preserve endothelial viability and barrier integrity in an in vitro blood–brain barrier model - Yoon-Young Hwang; Cho-Im Oh; Jin-Pyo Lee; Su-Min Lee; Dae-Young Park; In-Hwan Oh; Tae-rim Kim; Ok Chan Jeong; Ji-Young Ahn; Yang-Hoon Kim; Jiho Min (Molecular & Cellular Toxicology, 2026)

Risk assessment of benzophenone-3, a UV filter in cosmetics - Kyu-Tae Kang; Minhyuk Kim; Chi Rim Sung; Jung Dae Lee; Taehyung Yoon; Kyu-Bong Kim; Seung Jun Kwack; Joo Young Lee (Toxicological Research, 2026)

Lignin-tailored lignocellulose nanofiber films for light management using a deep eutectic solvent - Youngho Jeon; Kangyun Lee; Yuri Seo; Joonhoo Jung; Suji Lee; Seohyun Park; Hyeonjin Rim; Dongryul Kim; Jung Tae Lee; Jungmok You (Chemical Engineering Journal, 2025)

Al2O3-sheathed Si/Li2SiO3 nanocomposite anode materials for high-performance lithium-ion batteries - Donghan Youn; Ji Young Kim; Tae Rim Lee; Jiyoung Han; Sungjin Kim; Hansu Kim (Chemical Engineering Journal, 2025)

Production and characterization of a biodegradable polymer, poly(3-hydroxybutyrate-co-3-hydroxyvalerate), using the type II methanotroph, Methylocystis sp. MJC1 - Ok Kyung Lee; Seung Gi Kang; Tae-Rim Choi; Yung-Hun Yang; Eun Yeol Lee (Bioresource Technology, 2023)

Differential genetic diagnoses of adult post-lingual hearing loss according to the audiogram pattern and novel candidate gene evaluation - John Hoon Rim; Byunghwa Noh; Young Ik Koh; Sun Young Joo; Kyung Seok Oh; Kyumin Kim; Jung Ah Kim; Da Hye Kim; Hye-Youn Kim; Jee Eun Yoo; Seung-Tae Lee; Jin Woong Bok; et al. (Human Genetics, 2022)
Ski-slope hearing loss (HL), which refers to increased auditory threshold at high frequencies, is common in adults. However, genetic contributions to this post-lingual HL remain largely unknown. Here, we prospectively investigated deafness-associated and novel candidate genes causing ski-slope HL. We analyzed 192 families with post-lingual HL via gene panel and/or exome sequencing. With an overall molecular diagnostic rate of 35.4% (68/192) in post-lingual HL, ski-slope HL showed a lower diagnostic rate (30.7%) compared with other conditions (40.7%). In patients who showed HL onset before the age of 40, genetic diagnostic probability was significantly lower for ski-slope HL than for other conditions. Further analysis of 51 genetically undiagnosed patients in the ski-slope HL group identified three variants in delta-like ligand 1 ( DLL1 ), a Notch ligand, which presented in vitro gain-of-function effects on Notch downstream signaling. In conclusion, genetic diagnostic rates in post-lingual HL varied according to audiogram patterns with age-of-onset as a confounding factor. DLL1 was identified as a candidate gene causing ski-slope HL.

Genotypic Variation in Fatty Acids in Whole Grain Sesame (Fatty Acids in Whole Grain Sesame) - Qiang He; Tae-Rim Lee; Jie Yu; Win Htet Oo; Min-Young Yoon; Myeong-Hyeon Min; Sang-Ho Chu; Kyu-Won Kim; Young-Sang Lee; Yong-Jin Park (Journal of Crop Science and Biotechnology, 2020)

Calibration of the Pyranometer Sensitivity Using the Integrating Sphere - Bu-Yo Kim; Kyu-Tae Lee; Il-Sung Zo; Sang-Ho Lee; Hyun-Seok Jung; Se-Hun Rim; Jeong-Pil Jang (Asia-Pacific Journal of Atmospheric Sciences, 2018)

Correction to: Surface Downward Longwave Radiation Retrieval Algorithm for GEO-KOMPSAT-2A/AMI - Seo-Hee Ahn; Kyu-Tae Lee; Se-Hun Rim; Il-Sung Zo; Bu-Yo Kim (Asia-Pacific Journal of Atmospheric Sciences, 2018)

Surface Downward Longwave Radiation Retrieval Algorithm for GEO-KOMPSAT-2A/AMI - Seo-Hee Ahn; Kyu-Tae Lee; Se-Hun Rim; Il-Sung Zo; Bu-Yo Kim (Asia-Pacific Journal of Atmospheric Sciences, 2018)

Retrieval Algorithm for Broadband Albedo at the Top of the Atmosphere - Sang-Ho Lee; Kyu-Tae Lee; Bu-Yo Kim; ll-Sung Zo; Hyun-Seok Jung; Se-Hun Rim (Asia-Pacific Journal of Atmospheric Sciences, 2018)

Phototoxicity Evaluation of Pharmaceutical Substances with a Reactive Oxygen Species Assay Using Ultraviolet A - Yong Sun Lee; Jung-Sun Yi; Hye Rim Lim; Tae Sung Kim; Il Young Ahn; Kyungyuk Ko; JooHwan Kim; Hye-Kyung Park; Soo Jung Sohn; Jong Kwon Lee (Toxicological Research, 2017)

RNA-seq analysis of Rubus idaeus cv. Nova: transcriptome sequencing and de novo assembly for subsequent functional genomics approaches - Tae Kyung Hyun; Sarah Lee; Dhinesh Kumar; Yeonggil Rim; Ritesh Kumar; Sang Yeol Lee; Choong Hwan Lee; Jae-Yean Kim (Plant Cell Reports, 2014)

Oral Delivery of Ionic Complex of Ceftriaxone with Bile Acid Derivative in Non-human Primates - Ok-Cheol Jeon; Seung Rim Hwang; Taslim A. Al-Hilal; Jin Woo Park; Hyun Tae Moon; Seulki Lee; Jae Hyung Park; Youngro Byun (Pharmaceutical Research, 2013)

De novo transcriptome sequencing of Momordica cochinchinensis to identify genes involved in the carotenoid biosynthesis - Tae Kyung Hyun; Yeonggil Rim; Hui-Jeong Jang; Cheol Hong Kim; Jongsun Park; Ritesh Kumar; Sunghoon Lee; Byung Chul Kim; Jong Bhak; Binh Nguyen-Quoc; Seon-Won Kim; Sang Yeol Lee; et al. (Plant Molecular Biology, 2012)